Assessing Efficiency and Value Chain Performance in Rice Production: Insights from Bobonaro Municipality, Timor-Leste - Cristóvao Reis; Longuinhos Santos; Domingos Soares; Agostinho Coelho; Francisco Assis Lima (Business, Management and Economics: Research Progress Vol. 6, 2024)
The objective of this article is to evaluate the efficiency and performance of the rice production value chain in Bobonaro Municipality, Timor-Leste. Agriculture plays a key role in Timor-Leste’s development and social progress by occupying and sustaining the majority of the population. The domestic production of rice is totally destined for domestic consumption; it is insufficient to guarantee the supply of the basic food needs of the population, either for reasons associated with production reductions resulting from climatic adversities or by the constant decrease in productivity, or also by the increase in the population. The method used is the mixing method (quantitative and Qualitative) and primary data was sourced from 200 rice producers in one municipality, namely Bobonaro. The Data Envelopment + Analysis (DEA), Tobit, and Regression were estimated. The results showed that the production scale presented increasing returns of about 96%. Only 3% of the sample surveyed showed an efficient scale, and about 1% presented a production scale with decreasing returns. A comparison of the six most efficient and six least efficient rice producers in Bobonaro, focusing on the output of the rice agri-food value chain. The results of multiple linear regression analyses show that the model has a degree of adjustment of 60,63%, and the model is statistically significant. The estimated coefficients are statistically significant for land, seed, capital, and IR8 variety. There are many factors that influence the decision-making of producers when selling their rice products. Rice distribution chains operate through various channels, including traders, companies, wholesalers, retailers, and agents. A significant portion of value seekers prefer to buy in traditional and modern stores, suggesting an opportunity for value chain participants to redirect their efforts to meet modern retail standards. The actors in the value chain, especially producers, need a good policy from the government of Bobonaro municipality to improve the quality attributes of their rice fields, aligning their practices to the specific needs of consumers.